Faktor risiko lingkungan yang berhubungan dengan kejadian leptospirosis - Safitri, Retno Ayu; Fitriyani, Nur Lulu; Maulana, Jaya; Akbar, Hairil (Gema Wiralodra, 2023)
Leptospirosis is a zoonotic disease transmitted by rat vectors and caused by leptospira bacteria. This study aims to determine environmental risk factors that can influence the incidence of Leptospirosis. The method used in this study is a literature review. The literature sources used in compiling the literature review come from journals in 2018 - 2022 with an article search process via Google Scholar and PubMed. The results showed that environmental risk factors that influenced the incidence of leptospirosis included the presence of positive leptospira bacteria, the distance from the house to the gutters, the presence of standing water, the presence of trash cans, the presence of rats in and around the house, the presence of pets, the type of work. , history of injuries, history of water travel, use of PPE, condition of gutters, condition of trash cans, characteristics of houses not anti-rats, and history of activities at risk of leptospirosis.